Hyaluronan, CD44 and Emmprin: Partners in cancer cell chemoresistance - Toole, Bryan P. (2008)
Hyaluronan is not only an important structural component of extracellular matrices but also interacts with cells during dynamic cell processes such as occur in cancer. Consequently, interactions of hyaluronan with tumor cells play important cooperative roles in various aspects of malignancy. Hyaluronan binds to several cell surface receptors, including CD44, thus leading to co-regulation of signaling pathways that are important in regulation of multidrug resistance to anticancer drugs, in particular anti-apoptotic pathways induced by activation of receptor tyrosine kinases. Emmprin, a cell surface glycoprotein of the Ig superfamily, stimulates hyaluronan production and downstream signaling consequences. Emmprin and CD44 also interact with various multidrug transporters of the ABC family and monocarboxylate transporters associated with resistance to cancer therapies. Moreover, hyaluronan-CD44 interactions are critical to these properties in the highly malignant, chemotherapy-resistant cancer stem-like cells. Perturbations of the hyaluronan-CD44 interaction at the plasma membrane by various antagonists result in attenuation of receptor tyrosine kinase and transporter activities and inhibition of tumor progression in vivo. These antagonists, especially small hyaluronan oligomers, may be useful in therapeutic strategies aimed at preventing tumor refractoriness or recurrence due to drug-resistant sub-populations within malignant cancers.